Cellulolytic and Butyrivibrio fibrisolvens bacteria population density, after supplementing fodder diets (Pennisetum clandestinum) (2015)
ABSTRACT : Objective. Determine the population density of cellulolytic bacteria, Butyrivibrio fibrisolvens and the concentration of vaccenic acid, by supplementing diets consisting of kikuyu Grass (Pennisetumclandestinum Hoechst. Ex Chiov.) as base ingredient, together with cassava flour and biomass (effluent from ethanol production) in rumen simulator-Rusitec. Materials and methods. Four treatments (T) were evaluated, these were composed as: T1/Control 1: 100% kikuyu grass with a total protein intake of 23.9%, T2: a mixture of 70% kikuyu grass, 20% biomass and 10% cassava flour with a total protein intake of 19.4%; T3/Control 2: 100% kikuyu grass, with a 17.8% protein intake and T4: 70% kikuyu grass, 20% biomass and 10% cassava flour with a 15.3% protein intake. One and two-way variance analysis was made and the Pearson correlation coefficient was determined. Results. An increase was observed in the population density of viable cellulolytic bacteria (CFU/ml) and B. fibrisolvens statistically significant (p<0.005) with treatment T2, in contrast to T1, T3 and T4 treatments. In addition, there was a significant increase in the concentration of vaccenic acid (mg/L) in the ruminal content in Rusitec with the same treatment (T2). Conclusions. Results obtained in this ruminal simulation study are evidence to the benefits of kikuyu grass together with cassava flour and biomass diet implementation on the growth of ruminal cellulolytic and B. fibrisolvens bacteria, as well as on the production of vaccenic acid. The study also suggests the nutritional potential that such supplements could provide to grazing bovine feeding.